PET imaging studies to investigate functional expression of mGluR2 using [11C]mG2P001. Issue 2 (February 2023) - Yuan, Gengyang; Dhaynaut, Maeva; Guehl, Nicolas J; Neelamegam, Ramesh; Moon, Sung-Hyun; Qu, Xiying; Poutiainen, Pekka; Afshar, Sepideh; Fakhri, Georges El; Normandin, Marc D; Brownell, Anna-Liisa
Metabotropic glutamate receptor 2 (mGluR2) has been extensively studied for the treatment of various neurological and psychiatric disorders. Understanding of the mGluR2 function is pivotal in supporting the drug discovery targeting mGluR2. Herein, the positive allosteric modulation of mGluR2 was investigated via the in vivo positron emission tomography (PET) imaging using 2-((4-(2-[ 11 C]methoxy-4-(trifluoromethyl)phenyl)piperidin-1-yl)methyl)-1-methyl-1 H -imidazo[4, 5- b ]pyridine ([ 11 C]mG2P001). Distinct from the orthosteric compounds, pretreatment with the unlabeled mG2P001, a potent mGluR2 positive allosteric modulator (PAM), resulted in a significant increase instead of decrease of the [ 11 C]mG2P001 accumulation in rat brain detected by PET imaging. Subsequent in vitro studies with [ 3 H]mG2P001 revealed the cooperative binding mechanism of mG2P001 with glutamate and its pharmacological effect that contributed to the enhanced binding of [ 3 H]mG2P001 in transfected CHO cells expressing mGluR2. The in vivo PET imaging and quantitative analysis of [ 11 C]mG2P001 in non-human primates (NHPs) further validated the characteristics of [ 11 C]mG2P001 as an imaging ligand for mGluR2. Self-blocking studies in primates enhanced accumulation of [ 11 C]mG2P001. Altogether, these studies show that [ 11 C]mG2P001 is a sensitive biomarker for mGluR2 expression and the binding is affected by the tissue glutamate concentration.